Efeitos do envelhecimento e da osteoporose na cifose torácica, na propriocepção e no torque dos músculos do tronco. - Granito, Renata Neves (Universidade Federal de São Carlos, 2005)
The aim of this study was to evaluate the effects of aging and osteoporosis on thoracic kyphosis degree, on extensors and flexors trunk muscles torque and on proprioception. Moreover, this study investigated the possible correlation among the variables studied in this work. It was evaluated 40 voluntary women, divided in four distinct groups: Young Group (10 women) aged between 20 and 30 years old, Adult Group (10 women) aged between 40 and 50 years old, Old Group (10 women) aged more than 60 years old and Osteoporotic Group (10 women) aged the same as the previous group, however with diagnosis of osteoporosis on spine. The volunteers were submitted to a previous interview, to a bone densitometry to quantify the bone mineral density of lumbar spine and to an x-ray of the thoracic spine in lateral view to verify the thoracic kyphosis degree. Moreover, the volunteer were submitted to a proprioception evaluation and to the isokinetic test of the trunk muscles, both performed on the BIODEX SYSTEM 3 equipment. Data were statistically analyzed (p ≤ 0, 05). The results showed that thoracic kyphosis degree was significantly greater in the Osteoporotic Group, followed by the Old Group, Adult and the Young Group. It was found a significant reduction on the trunk extensor torque imposed by ageing and aggravated by osteoporosis. The ageing process was still responsible for a reduction on the trunk flexor torque, but this condition was not exacerbated by osteoporosis. The extensor torque was greater than the flexor, during both eccentric and concentric contractions, in both velocities of the isokinetic test. However, there were no significant differences between the groups on the extensor and flexor torque relation. The older volunteers, with and without osteoporosis, showed a greater proprioceptive deficit than the younger volunteers. It was found a significant negative correlation between bone mineral density with kyphosis degree and positive correlation between mineral density and trunk extensor torque. The thoracic kyphosis degree showed a negative correlation with the trunk extensor torque and a positive correlation with age and proprioceptive deficit. This study concluded that the physiologic aging process is responsible for an increased thoracic kyphosis, a reduction of the extensor and flexor trunk torques and a reduction of the proprioceptive sensibility. The osteoporosis amplifies the increase in thoracic kyphosis and the reduction on the trunk extensor torque imposed by age. However, the osteoporosis does not have any effect on the aging reduction of flexor torque of trunk muscles and on proprioceptive deficit.
v Effects of aging and osteoporosis on thoracic kyphosis, on proprioception and on trunk muscle torque.
Keywords: Fisioterapia; Osteoporose; Envelhecimento; Cifose torácica; Propriocepção; Avaliação isocinética; Osteoporosis; Aging; Toracic kyphosis; Proprioception; Isokinetics evaluation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL